Identification key of Ctenopoda (Cladocera, Holopedidae, Sididae) taxa from Brazil with remarks on taxonomy and geographic distribution - Sousa, Francisco Diogo R.; Elmoor-Loureiro, Lourdes M. A. (Zootaxa, 2021)
Using literature and field sampling data, we found that Brazilian fauna of the order Ctenopoda (Cladocera, Branchiopoda) was composed of twelve species, including the locally endemic Holopedium amazonicum and Sarsilantona behningi. In Brazil, Diapahanosoma (Neodiaphanosoma) bergamini was reported out of its type locality for the first time. Ctenopoda species were reported in all Hydrographic Regions in Brazil, however, the sampling effort was clearly distinct between many areas. These findings suggest the necessity of new faunal surveys in several parts of Brazil.